Anterior pallidal deep brain stimulation for Tourette's syndrome: a randomised, double-blind, controlled trial. Issue 8 (August 2017) - Welter, Marie-Laure; Houeto, Jean-Luc; Thobois, Stéphane; Bataille, Benoit; Guenot, Marc; Worbe, Yulia; Hartmann, Andreas; Czernecki, Virginie; Bardinet, Eric; Yelnik, Jerome; du Montcel, Sophie Tezenas; Agid, Yves; et al.
Summary: Background: Deep brain stimulation (DBS) has been proposed to treat patients with severe Tourette's syndrome, and open-label trials and two small double-blind trials have tested DBS of the posterior and the anterior internal globus pallidus (aGPi). We aimed to specifically assess the efficacy of aGPi DBS for severe Tourette's syndrome. Methods: In this randomised, double-blind, controlled trial, we recruited patients aged 18–60 years with severe and medically refractory Tourette's syndrome from eight hospitals specialised in movement disorders in France. Enrolled patients received surgery to implant bilateral electrodes for aGPi DBS; 3 months later they were randomly assigned (1:1 ratio with a block size of eight; computer-generated pairwise randomisation according to order of enrolment) to receive either active or sham stimulation for the subsequent 3 months in a double-blind fashion. All patients then received open-label active stimulation for the subsequent 6 months. Patients and clinicians assessing outcomes were masked to treatment allocation; an unmasked clinician was responsible for stimulation parameter programming, with intensity set below the side-effect threshold. The primary endpoint was difference in Yale Global Tic Severity Scale (YGTSS) score between the beginning and end of the 3 month double-blind period, as assessed with a Mann-Whitney-Wilcoxon test in all randomly allocated patients who received active or sham stimulation during the double-blind period. We assessed safety in all patients who were enrolled and received surgery for aGPi DBS. This trial is registered withClinicalTrials.gov, numberNCT00478842 . Findings: Between Dec 6, 2007, and Dec 13, 2012, we enrolled 19 patients. We randomly assigned 17 (89%) patients, with 16 completing blinded assessments (seven [44%] in the active stimulation group and nine [56%] in the sham stimulation group). We noted no significant difference in YGTSS score change between the beginning and the end of the 3 month double-blind period between groups (active group median YGTSS score 68·5 [IQR 34·0 to 83·5] at the beginning and 62·5 [51·5 to 72·0] at the end, median change 1·1% [IQR −23·9 to 38·1]; sham group 73·0 [69·0 to 79·0] and 79·0 [59·0 to 81·5], median change 0·0% [–10·6 to 4·8]; p=0·39). 15 serious adverse events (three in patients who withdrew before stimulation and six each in the active and sham stimulation groups) occurred in 13 patients (three who withdrew before randomisation, four in the active group, and six in the sham group), with infections in DBS hardware in four patients (two who withdrew before randomisation, one in the sham stimulation group, and one in the active stimulation group). Other serious adverse events included one electrode misplacement (active stimulation group), one episode of depressive signs (active stimulation group), and three episodes of increased tic severity and anxiety (two in the sham stimulation group and one in the active stimulation group). Interpretation: 3 months of aGPi DBS is insufficient to decrease tic severity for patients with Tourette's syndrome. Future research is needed to investigate the efficacy of aGPi DBS for patients over longer periods with optimal stimulation parameters and to identify potential predictors of the therapeutic response. Funding: French Ministry of Health.